Price-Cut and Consumer Behavior: A Qualitative Study of Buying Power in the Indonesian Market - Wangsa, Ign. Heri Satrya (Universitas Prasetiya Mulya, 2009)
The growing phenomena of price-cut reflect a reality that Indonesian consumers are very sensitive toward price (price-sensitive). On the contrary, there may have been pessimism that the pricing policy could potentially damage product quality as well as minimizing the benefit of core product in various consumer-oriented perspectives. This study intends to describe the phenomena of price-cut to explain arguments that the low level of buying power within the context of market in Indonesia could be questioning. The study uses focus group discussion among students at PTS “X” in Surabaya.